Scalable Lead Acetate-Based Perovskite Thin Films Prepared via Controlled Nucleation and Growth under Near Ambient Conditions - Sirkiä, Saara (American Chemical Society, 2025)
Lead acetate (PbAc2) is a promising precursor salt for large-scale production of perovskite solar cells, as its high solubility in polar solvents enables the use of scalable deposition methods such as inkjet printing and dip coating. In this study, uniform (40–230 nm) PbAc2 thin films were prepared via dip coating under near ambient lab conditions by tuning the PbAc2 precursor concentration. In a second step, these PbAc2 films were converted to methylammonium lead iodide (MAPI) perovskite by immersing them into methylammonium iodide (MAI) solutions. The nucleation and growth processes at play were controlled by altering key parameters, such as air humidity during the lead acetate deposition and MAI concentration when converting the PbAc2 film to MAPI. The research revealed that lead acetate is sensitive toward humidity and can undergo hydroxylation reactions affecting the reproducibility and quality of the produced solar cells. However, drying the PbAc2 films under low relative humidity (<1\%) prior to conversion enables the production of high-quality MAPI films without the need of glovebox processing. Furthermore, SEM characterization revealed that the surface coverage of the MAPI film increased significantly with an increase of the MAI concentration at the conversion stage. The resulting morphology of the MAPI films can be explained by a standard nucleation and growth mechanism. Preliminary solar cells were produced using these MAPI films as the active layer. The best performing devices were obtained with a 140 nm thick lead acetate film converted to MAPI using a 12 mg/mL MAI solution, as these parameters resulted in a good surface coverage of the MAPI film. The results show that the methodology holds potential toward large-scale production of perovskite solar cells under near ambient conditions, which substantially simplifies the fabrication and lowers the production costs.